2023
DOI: 10.7759/cureus.47585
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Inclusive Education in General Medicine Through the Perception of Medical Trainees: A Thematic Analysis

Ryuichi Ohta,
Takuji Katsube,
Chiaki Sano

Abstract: BackgroundGeneral medical education plays a pivotal role in ensuring holistic care in the context of rapidly aging populations. Japan's demographic trends underscore the significance of general medicine in elevating community care standards. Understanding and catering to the aspirations, perceptions, and ideals of medical students and residents can significantly augment the effectiveness of general medicine education. This research aimed to explore the perspectives of medical students on the ideal tenets of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…It is necessary to ensure that learners maintain ties to their primary institutions, enabling them to draw on previously acquired skills and knowledge [12,23]. Previous studies have shown that constant communication and reflection between medical teachers and learners improve their relationships in educational contexts and psychological safety in rural settings [24,25]. In rural contexts, teacher-learner relationships can be facilitated through regular virtual check-ins, case discussions, or integrating periods of returning to the primary institution as shared reading and continual reflection [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to ensure that learners maintain ties to their primary institutions, enabling them to draw on previously acquired skills and knowledge [12,23]. Previous studies have shown that constant communication and reflection between medical teachers and learners improve their relationships in educational contexts and psychological safety in rural settings [24,25]. In rural contexts, teacher-learner relationships can be facilitated through regular virtual check-ins, case discussions, or integrating periods of returning to the primary institution as shared reading and continual reflection [14].…”
Section: Discussionmentioning
confidence: 99%